Design of Greenhouse Microclimate Monitoring and Controlling System Based on Android - Pasimpangan , I Gusti Ayu Nadya Prasita; Widia , I Wayan; Wijaya , I Made Anom S.; Budisanjaya , I Putu Gede (Jurnal BETA (Biosistem dan Teknik Pertanian), 2022)
As the growth of development technology in agriculture, more automation technologies are used especially those applied to greenhouses. One of the uses of technology is automatic mircroclimate monitoring and controlling using sensor. Microclimate monitoringand controlling is important to maintain the plant’s environment so that it can grow optimally. The mircroclimates that were monitored and controlled in this research weretemperature, air humidity, and light intensity. The purpose of this research wastobuild amonitoring and controlling system for temperature, air humidy, dan light intensity in the greenhouse in an android smartphone connected to the internet. Arduino Mega 2560 wasused in this study as a microcontroller connected to DHT22 sensor and BH1750 sensor wereused to measure the mircroclimate automatically, ESP8266 as the wifi modul to link arduino and android via internet, as well as relayto control fan exhaust, LED grow light, and misting pumps as output control. This system wasequipped with an input setting point so user can adjust each microclimate according to the plant needs and control the output device automatically. The result of this research is a monitoring and controlling system in a greenhouse prototype with a length of 80 cm, 40 cm high, and 40 cm wide using the DHT22 sensors with an error of 2.2% for temperature measurement, 3,86% for air humidity measurement, and the BH1750 sensor which has been calibrated with 3,7% error for light intensity.The system can work properly where mircroclimare conditions can be monitored and controlled automatically from the application.